Reliability and clinical utility of the Pliance X for measuring pressure at the interface of pressure garments and burn scars in children. Issue 7 (November 2018) - Wiseman, Jodie; Simons, Megan; Kimble, Roy; Tyack, Zephanie
Highlights: Reliable, clinically acceptable devices are necessary to measure interface pressure. The Pliance X has close to acceptable reliability with children post burn. The Pliance X is clinically acceptable for children who are not distressed. Abstract: Background: Reliable, clinically acceptable pressure measuring devices are important to accurately record interface pressure. The Pliance X is a device that may overcome previous device limitations (i.e. pressure garment distortion, temperature dependent sensors). This research aimed to identify the test–retest reliability and clinical utility of the Pliance X in children receiving pressure garment therapy post-burn. Methods: Data was collected as part of a pilot longitudinal cohort study. Immediate test–retest reliability was investigated at baseline and analysed using Intra-Class Correlation Coefficients (ICCs). Clinical utility was evaluated at baseline using the criteria of appropriate, accessible, practicable and acceptable. Results: Thirty-one children completed baseline measurements. Participants had a median age of three years (IQR: 1.5, 7.5), and 61% were male. Test–retest reliability of the Pliance X was close to acceptable for clinical use for stationary interface pressure (ICC = 0.87, n = 27). The Pliance X was appropriate and acceptable for children of all ages who were not distressed. Discussion: Further reliability testing is required, including inter-rater reliability testing. The device's clinical utility could be improved with alternate sensor styles and an instant mean pressure reading to enable immediately clinically useful information on the interface pressure.